Review on ginger (Zingiber officinale Roscoe): phytochemical composition, biological activities and authentication analysis - Styawan, A. A.; Susidarti, R. A.; Purwanto, Purwanto; Windarsih, A.; Rahmawati, N.; Sholikhah, I. K. M.; Rohman, A. (Rynnye Lyan Resources, 2022)
Zingiber officinale Roscoe, known as ginger has been widely used as a spice in food application and as a herbal component in traditional medicine. Its rhizome is known to have bioactive compounds such as phenolic compounds, flavonoid compounds, and essential oils which are responsible for pharmacological activities. Gingerol is the major phenolic compound in the ginger rhizome which consist of gingerol, shogaol, paradol, zingerol, gingerones, and gingerdiones. Other compounds such as polysaccharides, amino acids, organic acids, and minerals are also present. Ginger provides health advantages for humans because of its biological activities such as antioxidant, antiinflammation, antibacterial, antiviral, antifungal, antihyperlipidemic, antiobesity, and hepatoprotective activities. Products developed from ginger rhizomes were used in foods, beverages, and herbal medicine. Due to its functional values and its wide application, it is very important to ensure its authenticity. Authentication is important for quality control because it is related to the safety, efficacy, and quality of the products. The high-performance liquid chromatography (HPLC), DNA-based method, and vibrational spectroscopy combined with chemometrics of multivariate analysis have been successfully used for ginger authentication. This review highlighted the phytochemical compositions, biological activities, and authentication analysis of ginger rhizome. Based on its biological activities, ginger is a good source of pharmaceutical and nutraceutical products. © 2022 The Authors.